1981
DOI: 10.1148/radiology.141.1.7291547
|View full text |Cite
|
Sign up to set email alerts
|

Amputated calcified ovaries in children.

Abstract: A calcified abdominal mass was an identical finding in four asymptomatic girls, ages 2 weeks to 9 years. At laparotomy the right ovary was absent, and in three patients the ipsilateral oviduct was at least partially absent. The most likely explanation is antenatal or subclinical torsion of the adnexa with subsequent amputation, necrosis, and calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
39
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…T h e r a d i o g r a p h i c a n d u l t r a s o u n d f i n d i n g s c o r r e l a t e d very closely w i t h t h e o p e r a t i v e a n d histologic features. I n this p a p e r we r e p o r t these t w o n e w cases w i t h a d d i t i o n a l f i n d i n g s o n o n e o f t h e p a t i e n t s r e p o r t e d b y K e n n e d y et al [8].…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…T h e r a d i o g r a p h i c a n d u l t r a s o u n d f i n d i n g s c o r r e l a t e d very closely w i t h t h e o p e r a t i v e a n d histologic features. I n this p a p e r we r e p o r t these t w o n e w cases w i t h a d d i t i o n a l f i n d i n g s o n o n e o f t h e p a t i e n t s r e p o r t e d b y K e n n e d y et al [8].…”
mentioning
confidence: 87%
“…[8], case 1). A 17-month-old girl, was found to have a non-tender right upper quadrant mass on routine physical examination.…”
mentioning
confidence: 96%
“…7 In cases of simple cysts larger than 5 cm in diameter and complex cysts, surgical removal of the mass is most often recommended. 8 Kennedy et al first reported the autoamputation of ovarian cysts in infants under 1 year of age, and noted that it is extremely rare. 8 Its diagnosis and treatment have not been clearly established due to its rarity.…”
Section: Discussionmentioning
confidence: 99%
“…8 Kennedy et al first reported the autoamputation of ovarian cysts in infants under 1 year of age, and noted that it is extremely rare. 8 Its diagnosis and treatment have not been clearly established due to its rarity. There have only been 13 reported cases of autoamputated ovarian cysts in infants under 1 year of age including our case, and only one of these cases was diagnosed as an autoamputated ovarian cyst preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Torsion and infarction of an ovary normally leads to autoamputation and may indeed result in calcification (Fletcher et al, 1988). In modern literature, such calcified ovaries are most frequently reported in children, but are considered to be a rare pathology (Lester & McAlister, 1970;Kennedy et al, 1981;Fletcher et al, 1988), while myomae of the uterus are more frequently diagnosed. It would thus be highly unlikely that the biological concretions found in the different graves of the cemetery of the nunnery are ovarian fibroids.…”
Section: Discussionmentioning
confidence: 99%